Optimal Design and Distribution of Viscous Dampers for Shear Building Structures Under Seismic Excitations - Cetin, Huseyin; Aydin, Ersin; Ozturk, Baki (Frontiers in Built Environment, 2019)
Viscous dampers (VDs) are effective and widely used passive devices for the protection of civil structures, provided that appropriate design is carried out. For this purpose, optimal design and optimum distribution of VDs method are presented for a shear building under the critical excitation by using random vibration theory in the frequency domain. In the optimization, by using Differential Evolution (DE) algorithm and the top floor displacement are evaluated as objective functions taking into consideration upper and lower limits of VDs damping coefficients, so that optimal damper placement and properties of the shear building can be determined. In this design, the VDs-shear building system is tested under the three different ground motions being compared to some methods in the literature and uniformly distributed VDs placed at each story. It is shown that the results of the study are both compatible and very successful in reducing the response of the structure under the different ground motions.